G103 That's what chums are for – benefits of a medical student paediatric volunteering service. (12th March 2018) - Stokes, V; Horton, O; Nolan, E; Ashton, C; Edwards, C; Parsons, S; Davis, N; Jameson, E
Abstract : Aims: Medical students from the University of Manchester interested in a paediatric career started a society called CHUMS (Children's Hospital University of Manchester Students). The primary aim was to improve patient and parent/carer experience by providing play sessions at Royal Manchester Children's Hospital (RMCH). A secondary aim was to assess the impact sessions had on patient mood and pain scores. Methods: CHUMS is run by a student committee and is a recognised University society. It is overseen by two RMCH paediatric consultants and is supported by the Trust's 'Transform Together' team. Student volunteers are recruited through an application process and undergo play therapy training. Volunteers attend 4 of the 7 wards and PED. Questionnaires are collected from the children to assess their mood (range: very unhappy to very happy) and pain scores (range: 0: no pain to 9: worst pain) before and after the session. Parent/carer questionnaires are collected to assess quality and appropriateness of sessions. Wilcoxon signed-rank tests were performed to compare scores. Results: CHUMS has provided weekly, 2 hour, evening play sessions during the academic year since 2013. A total of 111 parent/carer, 80 0–12 year old and 33 12–16 year old questionnaires were collected. Primary Aim CHUMS is very popular with the children, especially the long term patients. 92% of parents/carers strongly agree their child enjoys time with the volunteers; 96% wish volunteers could spend more time with their child. Secondary Aim significant improvement is seen in pain and mood scores in both age groups; most notable are pain scores in 0–12 year olds with mean score improving from 2.39 before to 1.56 after the session (p=0.002). Conclusion: CHUMS has received tremendous feedback from all involved and has won the PiccaLilly award from the NHS 'Academy of Fabulousness'. It has demonstrated effectiveness in its primary and secondary aims. Its success has inspired a similar initiative, known as Hospital Buddies, on the stroke ward at Manchester Royal Infirmary.